Petrology and geochronology of ultrahigh-pressure granitic gneiss from South Dulan, North Qaidam belt, NW China. Issue 2 (25th January 2016) - Ren, Yunfei; Chen, Danling; Hauzenberger, Christoph; Liu, Liang; Liu, Xiaoming; Zhu, Xiaohui
Abstract: An integrated study including petrography, mineral chemistry, metamorphic P–T path modelling, and zircon U–Pb dating was conducted on a granitic gneiss and enclosed eclogite from South Dulan, North Qaidam UHP (ultrahigh-pressure) belt. The result shows that the granitic gneiss underwent a clockwise P–T path with a peak-P stage at 655–745°C, 30–34 kbar, and a subsequent peak-T stage at 815–870°C, 14–18 kbar, which is similar to the P–T estimates reported for coesite-bearing continental-type eclogites in this region. The enclosed eclogite resembles an olivine–pyroxene-rich cumulate in Qaidam block. It has a similar prograde P–T path with the country gneiss and experienced a peak-P stage of 682–748°C at 27–34 kbar. Zircon U–Pb dating yields an eclogite-facies metamorphic age of 447 ± 2 Ma for the granitic gneiss and 445 ± 6 Ma for the enclosed eclogite. These ages agree with metamorphic ages obtained from paragneisses (427–439 Ma), coesite-bearing continental-type eclogites (430–451 Ma), and UHPM (ultrahigh-pressure metamorphic) oceanic crust–mantle sequence (440–445 Ma) from South Dulan, as well as UHP eclogites, garnet peridotite, and gneisses from other units (460–420 Ma) within this belt reported by others. Similar metamorphic ages as well as P–T evolution documented in gneisses and intercalated eclogites imply that both rocks experienced a coeval UHP event. Summarizing all the published geochronology data, we argue that the North Qaidam UHP belt was mainly formed by continental deep subduction at 460 to 420 Ma. The UHPM oceanic crust-mantle sequence in South Dulan may represent oceanic lithosphere in the transition zone between oceanic and continental crust, which was dragged upward by the exhumed continental rocks after break-off of the dense oceanic crust.